AYURVEDIC MANAGEMENT OF KITIBHA W.S.R. TO PSORIASIS - Gupta, Manoj Kumar; Kanungoo, Neeraj; Sharma, Sandhya; Gaur, Dinesh Singh (Innoriginal: International Journal of Sciences, 2014)
Objective Following are the aims and objectives of the dissertation. For study the aetiology, pathology, symptomatology and progress of the disease. Nidan Panchak and predominance of Doshas according to Ayurvedic as well as modern medical science and to analyse the efficacy of Virechan karma on Kitibha.Analyse the efficacy of the ayurvedic drug Navayas Rasayanan yog (5 gm. BID) and virechana karma on Kitibha or Psoriasis after purification of the body ( Shodhan puravaka Shaman chikitsa). Compare the effect of ayurvedic drug Navayas Rasayanan yog (5 gm. BID) both Group A & Group B without purification (shaman chikitsa) and after purification (shodhan purvaka shaman chikitsa). Group C worked as a placebo group (2 capsules Godanti Bhasma/day). Method The present clinical study has been divided into three groups to analyses the efficacy and clinical comparative study of both the therapies on kitibha/psoriasis. Group A- This is Shodhan group virechana karma was given to patients of this group. After samsarjan karma placebo was given up to the 30 days. Group B- This is Shodhan purvaka shaman group. Virechana was followed by administration of Navayas Rasayan yog in the dosage of 5 gm. BID after Samsarjan karma. The total therapy is carried out by 30 days. Group C-This is Shaman group. Navayas Rasayan yog was given to the patients of the group in the dosage of 5 gm. BID for 30 days Results All the results obtains of subjective and objective parameter of the psoriasis during before treatment and after treatment of clinical trial has been noted and assess the effect of given drug Navasyas Rasayan Yog Dose5 gm. BID with lukewarm water on the patients of group B after Snehana Svedan Puravak Virechan karma was performed (Shodhan puravak shaman therapy) . Where as in the patients of Group A Snehana Svedan Puravak Virechan karma was performed. After that dispensing of capsule of placebo in forms of Godanti Bhasma Dose – 2 Capsules BID (125mg=1capsules) has been given in the patients of Group A. Only Shaman Therapy Navasyas Rasayan Yog Dose 5 gm. BID with lukewarm water on the patients of Group C has been given without Snehana Svedan Puravak Virechan karma was performed in the patients of psoriasis of Group C. Scoring (PASI Score) Psoriasis area severity index score It has been employed in numerous clinical trials to assess difference between before and after treatment in a fairly vigorous and consistent manner that is reproducible between investigators and the centres. The four main anatomic sites are assessed 1- the head (h), 2-upper extremities (u), 3-lower extremities (l), 4-trunk (t).PASI scores were introduced for studies of synthetic retinoid in 1978.it had been calculated as follows. PASI=0.1(Eh+Sh+Ih) Ah+0.2(Eu+Su+Iu) Au+0.3(Et+St+It) At+0.4(EI+SI+II) AI. Where-E=Erythema, S=Scaling, I=Indurations, A=Area.PASI score was completed on the basis of its severity index such Erythema, Induration and scaling, and for Area. Score by percentage grading as mentioned in materials and methods.Mean changes in PASI score in different groups after therapy with trial drugs by Navayas Rasayanas, Virechan and Shodhan Poorvak Shaman group though produced a statically significant change the overall reduction of PASI score only 1.28 + 1.40 and by Navayas rasaya and 6.64 + 5.62 by Shodhan Poorvak Shaman group. Group C suggests that Navayas rasayan has got small but consistent effect of PASI score, while C Shodhan Poorvak Shaman group has good result.In Group A no. of patches were reducing by 46.21% and 54.4% no. of patches reduced in Group B while in Group C it was reduced by 48.5% all the result were highly significant. All three groups gave very good relief to the patients, though very good relief to the patients, though symptom was assuaged more in Group B shodhan poorvak shaman group. Conclusion Complete remission was found in 20% in Group A, 60% in Group B and 50% Group C. As a whole of 30 pt. studied, complete remission was found in 43%. Markedly improvement was obtained in 30% in Group A, 30% pt of Group B and 20% pt. of Group C. Of the 30 pt. studied, markedly improvement was found in 26.7%. Improvement was found in 40% of Group A, 30% of Group B and 30% Group C pt. of the 30 pt. studied improvement was found in 26.7%. 10% of pt. of Group A only remains unchanged.